Analisis Potensi Peningkatan Minat Kunjung Pemustaka di Dinas Perpustakaan dan Kearsipan Kabupaten Bantul - Ari Kristanti, Melisa; Santoso, Budhi (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research was conducted at the Bantul Regency Library and Archives Service. The aim of this research is to analyze the increasing interest in visiting the Bantul Regency Library and Archives Service from year to year. This research uses qualitative descriptive methods with data collection techniques, namely Observation, Interviews, Documentation. Systematically observe and record the situation at the Library and Archives Service Bantul Regency and conducted interviews with librarians and several library visitors. This research proves what factors cause increased interest in visiting the Bantul Regency Library and Archives Service. The results of this research indicate that there are 2 factors increasing interest in visiting the Bantul Regency Library and Archives Service, namely Internal Factors and External Factors.